Research on Data Security Measures in Romania - Popescu, Mirona Ana Maria; Barbu, Andreea; Simion, Petronela Cristina; Moiceanu, Georgiana (Proceedings of the ... International Conference on Business Excellence, 2024)
Information from the online environment is constantly increasing, as well as its value. In this context, for companies data security becomes a central pillar to protect sensitive information and to ensure its integrity, confidentiality and availability (CIA Triangle). The security measures adopted by the companies also increase the degree of trust of their partners and customers. But data security is not just about implementing the right technologies and policies; equally important is the awareness and proper training of personnel who interact with this data or the applications that contain it. Human resource in companies playes an important role in protecting sensitive information by understanding the negative conseques of not securing and manipulating in a risky manner the confidential data used in their daily activies. To prepare the human resource and educate the employees in order to raise their awarness towards which is considered sensitive data, what measures and tools must be applied when handling it, trainings by specialisez personnel can be implemented. In this manner, the risks of cyber security attacks, data leak, are minimized and the business environment is strengthened. In this research it is presented a review of specialized literature that treat the subject of data security to highlight the current stage of development and have a general landscape from a scientific point of view. Having this as a base, the authors have developed a questionnaire that was distributed to romanian companies to find out the business perspective towards this subject. Therefore, by analysing the two perspectives, this study has the goal to present the dynamics of data security, the challenges brought by it and the good practices that can be addopted.